2015
DOI: 10.1016/j.ejr.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical atherosclerosis and peripheral vascular disease in systemic sclerosis patients: Relation to potential risk factors

Abstract: Aim of the work: To measure the extent of subclinical atherosclerosis in patients with systemic sclerosis, and to evaluate any potential vascular risk factors in these patients.Patients and methods: This study included 30 patients with systemic sclerosis diagnosed according to the American college of rheumatology criteria and 20 healthy individuals were also included as a control group. Non-invasive vascular tests including; carotid duplex scanning measuring common carotid arteries (CCA) intima-media thickness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
1
1
Order By: Relevance
“…On the other hand, no significant associations were found between the presence of macrovascular involvement and the sedimentation and blood glucose values. The authors reported they found no relationship between disease subtypes 24 . The fundamental differences between the results of our study and these studies can be listed as follows: the limited number of patients in our control group, the majority of our cohort comprising of the limited subtype of SSc, and the rather low levels of disease severity scores in our patients.…”
Section: Discussioncontrasting
confidence: 73%
“…On the other hand, no significant associations were found between the presence of macrovascular involvement and the sedimentation and blood glucose values. The authors reported they found no relationship between disease subtypes 24 . The fundamental differences between the results of our study and these studies can be listed as follows: the limited number of patients in our control group, the majority of our cohort comprising of the limited subtype of SSc, and the rather low levels of disease severity scores in our patients.…”
Section: Discussioncontrasting
confidence: 73%
“…Although we have previously reported an impaired lipid profile in different SSc settings [14][15][16][17][18][19], available data on total cholesterol and its fractions, low-density and highdensity lipoprotein cholesterol, triglycerides and lipoproteins (A, B) in SSc subsets is controversial [20][21][22][23][24][25]. Thus, decreased HDL-cholesterol was detected in patients with limited cutaneous disease, while abnormal values in other studies performed in SSc [20][21][22][23][24][25].…”
Section: Correlation Between Lipid Metabolism Periodontal Disease Anmentioning
confidence: 99%